2012
DOI: 10.1186/1471-2164-13-s8-s21
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the status of genetic lesions in cancer clinical trial documents using machine learning

Abstract: BackgroundMany cancer clinical trials now specify the particular status of a genetic lesion in a patient's tumor in the inclusion or exclusion criteria for trial enrollment. To facilitate search and identification of gene-associated clinical trials by potential participants and clinicians, it is important to develop automated methods to identify genetic information from narrative trial documents.MethodsWe developed a two-stage classification method to identify genes and genetic lesion statuses in clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In this project, we adopted a word sense disambiguation system developed in our previous work to determine ambiguous gene mentions in clinical trial documents. 7 We leveraged the previous training samples and modified the existing system to classify candidate gene mentions into 3 categories: "Gene-related" (eg, PTEN gene mutation), "Drug" (eg, no prior EGFR-inhibitor therapy), and "Others" (eg, patient met the criteria).…”
Section: Research and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this project, we adopted a word sense disambiguation system developed in our previous work to determine ambiguous gene mentions in clinical trial documents. 7 We leveraged the previous training samples and modified the existing system to classify candidate gene mentions into 3 categories: "Gene-related" (eg, PTEN gene mutation), "Drug" (eg, no prior EGFR-inhibitor therapy), and "Others" (eg, patient met the criteria).…”
Section: Research and Applicationsmentioning
confidence: 99%
“…In our previous studies, we developed machine learning-based methods to detect genetic status from cancer trials by working with MyCancerGenome.org and IPCT data. 7,8 However, our previous studies were relatively small pilot projects that focused on methodology development and evaluation for intermediate tasks such as word sense disambiguation. In this study, we developed an end-to-end system that takes ClinicalTrials.gov documents as inputs and generates annotations of genetic alterations in all cancer trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLAD4U ensures computational efficiency through the effective use of existing NCBI resources, which also made it one of the winning applications in the National Library of Medicine (NLM)'s 2011 Software Development Challenge on the Innovative Uses of NLM Information. Wu et al, [26] developed a two-stage classification method for identifying genes and genetic lesion statuses in clinical trial documents. Their system was initially developed and tested on individually annotated genes and later was expanded to all genes in cancer trial documents.…”
Section: Bmc Genomics Supplement Issuementioning
confidence: 99%
“…Our prior approaches to clinical trial annotation explored both key word search 14 and natural language processing (NLP)-based approaches 10 for automated extraction of biomarker eligibility criteria from clinical trial documents. However, we and others with similar efforts concluded that the level of precision and recall achieved by these methods is relatively low.…”
Section: Introductionmentioning
confidence: 99%